TMEM126A mutation in a Moroccan family with autosomal recessive optic atrophy - Désir, Julie (Molecular Vision, 2012)
PURPOSE: Nonsyndromic autosomal recessive optic atrophy (arOA) is extremely rare and its existence was disputed until a locus, optic atrophy 6 (OPA6), was mapped to 8q. Recently, a second locus, OPA7, was found on 11q in several families from North Africa, with one presumably ancestral mutation of transmembrane protein 126A (TMEM126A). Here we report an independently ascertained large consanguineous family of Moroccan descent with three siblings affected with nonsyndromic arOA. METHODS: Assuming autosomal recessive inheritance, we identified a locus on 11q with homozygosity mapping, with a multipoint logarithm of the odds score of 3.84, and sequenced two candidate genes. Direct sequencing of the complete coding sequence of TMEM126A revealed mutation p.Arg55X, homozygous in all affected siblings and heterozygous in both unaffected parents. RESULTS: This mutation was identical to that recently reported in families from North Africa, consistent with a single ancestral origin. In contrast to the recently reported patients, however, the siblings reported in this study had a relatively mild clinical course, with sudden onset in adolescence in the proband. Interestingly, the proband, but not the other affected siblings, had sensory-motor axonal neuropathy with electrophysiological data strongly suggestive of focal demyelinating abnormalities. An unaffected sibling had transient loss of vision after exercise, i.e., Uhthoff's sign of optic neuropathy, and was found to be a heterozygous carrier of the mutation. CONCLUSIONS: Our results confirm genetic heterogeneity in arOA, illustrate clinical variability between families with the p.Arg55X mutation including the description of a mild phenotype in a heterozygote, and underscore the implication of mitochondrial proteins in optic and peripheral neuropathy.